Extension science : information systems in agricultural development - Roling, Niels G. (Cambridge University P. CambridgeGB, 1988)
Traces development of extension science and discusses an information system which dynamically integrates agricultural research, extension and farmers. Examines the mechanism of extension as an instrument for inducing voluntary change. Discusses use of diffusion of innovations research methods for identifying homogeneous target categories in rural areas. Explores the macro context of extension and argues case for targetting. Provides results of a field experiment which targetted extension on`forgotten farmers' in Kenya. Discusses creation of active farmer systems and the agricultural information system as a tool for analysis and design of agricultural research, extension and agricultural knowledge utilization.